Factors Contributing to the Upward Transfer of Baccalaureate Aspirants Beginning at Community Colleges - Wang, Xueli (My University, 2010)
Incorporating the psychological perspective, this study examines factors associated with the upward transfer of baccalaureate aspirants beginning at community colleges. Based on data from the National Education Longitudinal Study of 1988 and the Postsecondary Education Transcript Study, the study tests a logistic regression model to predict bachelor's degree-seeking community college entrants' transfer to four-year institutions. The results indicate that students' socioeconomic status, identification as African American, self-concept, high school test scores, and postsecondary enrollment patterns are significantly associated with the probability of transfer to four-year institutions among baccalaureate aspirants.
Keywords: Two-Year Institutions; Access, Persistence, and Success